Content area reading and literacy : succeeding in today's diverse classroom - Alvermann, Donna E.; Phelps, Stephen F.; Gillis, Victoria Ridgeway; Alvermann, Donna E. (Boston, Mass. : Allyn & Bacon, 2010)
A continuing best-seller, the Sixth Edition of'Content Area Reading and Literacy'equips preservice and inservice teachers to teach content area literacy in an era of high accountability and provides in-depth and integrated attention to the needs of students from diverse cultural and language backgrounds. This well-respected text has been lauded for its scope of topics and examples, its research-based information, and its accessible writing style. Written by trusted authorities in the field of adolescent literacy, Donna Alvermann, Stephen Phelps, and Victoria Ridgeway Gillis, the sixth edition includes up-to-date information on addressing the literacy needs of English learners and a culturally diverse student population. Victoria Ridgeway Gillis has more than two decades of secondary school teaching experience, which brings added depth and credibility to each chapter. This text also addresses new frameworks for reading and writing instruction, including a sociocultural perspective on teaching and learning and insights from the New Literacies. -- Description from http://www.booktopia.com.au (Nov. 3, 2011)
A continuing best-seller, the Sixth Edition of'Content Area Reading and Literacy'equips preservice and inservice teachers to teach content area literacy in an era of high accountability and provides in-depth and integrated attention to the needs of students from diverse cultural and language backgrounds. This well-respected text has been lauded for its scope of topics and examples, its research-based information, and its accessible writing style. Written by trusted authorities in the field of adolescent literacy, Donna Alvermann, Stephen Phelps, and Victoria Ridgeway Gillis, the sixth edition includes up-to-date information on addressing the literacy needs of English learners and a culturally diverse student population. Victoria Ridgeway Gillis has more than two decades of secondary school teaching experience, which brings added depth and credibility to each chapter. This text also addresses new frameworks for reading and writing instruction, including a sociocultural perspective on teaching and learning and insights from the New Literacies. -- Description from http://www.booktopia.com.au (Nov. 3, 2011)
Content Literacy and the Reading Process --- Language, Diversity, and Culture --- Creating a Favorable Learning Environment --- Planning for Content Literacy --- Assessment of Students and Textbooks --- Preparing to Read --- Reading to Learn --- Increasing Vocabulary and Conceptual Growth --- Reflecting on Reading --- Writing Across the Curriculum --- Studying and Study Strategies --- Developing Lifetime Readers: Literature in Content Area Classes.
Includes bibliographical references (p. 435-465) and indexes.
Keywords: Content area reading -- United States; Reading (Secondary) -- United States; Multicultural education -- United States; Reading (Secondary) -- Social aspects -- United States; Teenagers -- Books and reading -- United States; Content area reading -- United States -- Textbooks; Reading (Secondary) -- United States -- Textbooks; Multicultural education -- United States -- Textbooks; Reading (Secondary) -- Social aspects -- United States -- Textbooks; Teenagers -- Books and reading -- United States -- Textbooks